The effectiveness of neurofeedback therapy on emotional regulation and anger in 11- and 12-year-old adolescent boys with anxiety disorders - Parisa Mazahi; Arezoo Shomali Oskoei; Mehdi Roozbahani (روانشناسی و روانپزشکی شناخت, 2025)
Introduction: Adolescents with anxiety disorders exhibit high levels of anger and emotional dysregulation. Neurofeedback seems to be one of the effective interventions in this field. Aim: The present study aimed to determine the effectiveness of neurofeedback therapy on emotional regulation and anger in 11- and 12-year-old adolescent boys with anxiety disorders. Methods: The research method was semi-experimental with a pre-test-post-test-follow-up design with a control group. The statistical population of this research included all 11- and 12-year-old boys with anxiety disorders who were referred to clinics and psychotherapy centers in 2022, out of which 34 adolescents were selected by available sampling method and randomly and by homogenizing age and type of anxiety disorder, they were placed in two experimental and control groups. The research tool for the pre-test-post-test and follow-up was the emotion regulation difficulties scale and state and trait anger expression inventory. The neurofeedback therapy method was implemented using devices equipped with a computer system in 20 45-minute sessions for each person in the experimental group. Analysis of variance with repeated measurements was used to analyze the data. Results: The results showed that neurofeedback therapy had a reducing effect on the difficulty of emotion regulation (P=0.001). Neurofeedback therapy had a reducing effect on anger (P=0.001). The results also showed that the effectiveness of neurofeedback on the difficulty of regulating emotion and anger was sustained over time (P=0.001). Conclusion: The results showed that neurofeedback therapy is effective on emotion regulation and anger in 11- and 12-year-old adolescent boys with anxiety disorders. It is recommended to use useful therapeutic approaches such as neurofeedback for children and adolescents with anxiety disorders in treatment centers.